1, 3, 5‐Trisubstituted Pyrazoles as Potent Negative Allosteric Modulators of the mGlu2/3 Receptors. (10th April 2017) - Van Gool, Michiel; Alonso De Diego, Sergio A.; Delgado, Oscar; Trabanco, Andrés A.; Jourdan, Fabrice; Macdonald, Gregor J.; Somers, Marijke; Ver Donck, Luc
Abstract: The metabotropic glutamate subtype 2 (mGlu2 ) receptor is a presynaptic membrane receptor distributed widely in brain that provides feedback inhibitory control of glutamate release. Inhibition of the mGlu2 receptor function with a negative allosteric modulator (NAM) enhances activity‐dependent glutamate release, which may be of therapeutic benefit for the treatment of neurological and psychiatric disorders. An attractive pyrazole hit was identified after a high‐throughput screening (HTS) campaign. The evolution of this hit is described by structure–activity relationship (SAR) studies on specific parts of the molecule. From near micromolar potency we could obtain compounds with single‐digit nanomolar activity in the mGlu2 NAM GTPγS assay. In addition to SAR on in vitro potency, a more detailed overview is given with a specific set of compounds on the excellent agreement between in vitro potency, free brain concentration, and ex vivo mGlu2 receptor occupancy. Finally, to obtain improved drug‐like compounds, plans for future research are suggested toward increasing free brain concentration while maintaining high in vitro potency. Abstract : Much positive in the negative : A medicinal chemistry exploration of the high‐throughput screening hit1 resulted in compounds17 and19, both of which have single‐digit nanomolar potency against the metabotropic glutamate 2 receptor (mGluR2 ) and excellent correlation with unbound brain fraction at ED50 from ex vivo occupancy assays. These findings support the development of mGluR2 negative allosteric modulators (NAMs) to treat neurological and psychiatric disorders.